11 Flabra, frontline approach for BRCA testing in ovarian cancer (OC) treatment naïve population. A latin america (LA) epidemiologic study. (18th September 2019) - Goncalves, S; Gomez Abuin, G; Gallardo, D; Estevez Diz, P; Caceres, V; De la Vega, M; Palazzo, F; Lerzo, G; Kaen, D; Gerson, R; Lim, M; Philco, M; et al.
Abstract : Objectives: Previously described prevalence of BRCA mutated OC is 14% for germline BRCA mutations (gBRCA M ), that could increase to 20% considering somatic BRCA mutations (sBRCA M ). Latinamerican population is a paradigm of poly-ethnicity and ancestries and the prevalence of BRCAm is unknown. FLABRA is a cross-sectional, multi-center study designed to determine the prevalence of BRCAm, either sBRCA M or gBRCA M in high grade serous OC LA patients, with a new approach of start testing in tumor. We also aimed to describe current genetic counselling and treatment approach at frontline in this population. Methods: We enrolled 407 patients from Argentina, Brazil, Colombia, Mexico, Peru and Panama, diagnosed with OC within the last 120 days. Archived tumor blocks or 10-µm sections were used for BRCA testing in tissue (Myriad Tumor BRACAnalysis CDx™). Patients who were positive in tumor, were analysed in blood to determine if the mutation was from germline (Myriad Single Site BRACAnalysis®). In gBRCA M, genetic counseling was advised. Patients medical records were reviewed for data relevant to medical history, OC diagnosis, counseling approach, and treatment plan. Results: Results from first 376 patients who already completed the study: BRCA mutations prevalence detected in tumor was 30%. Conclusions: Our data show a high prevalence of sBRCAM and gBRCAM in LA OC pts. Additionally, this new approach of start testing the tumor may prove to be more cost effective, leading to a more conclusive result; so refinement of this technique is a must. The high prevalence of sBRCAM in certain regions of LA needs to be further investigated.